The Gender Diferentiation of Psychological Characteristics of Problem Children’ Parents - Mushkevych, Myroslava (Psychological Prospects Journal, 2018)
The article describes the importance of studying the peculiarities of the personal and family functioning of problem child’ parents. It is indicated that the category «problem children» includes those that create inconveniences for the functioning of adults (parents, ancestors, teachers, others), as they are characterized by shyness, excessive activity, aggressiveness, inattention, disobedience, tearfulness, anxiety, impulsivity, closure, irresponsibility, etc. (aged 5 to 9 years). The initial empirical factogue for analysis was the psychological characteristics of the subjects, measured by a set of psychodiagnostic means: the projective test «Self-portrait» (O. Kandaurov), the projective test «The non-existent animal» (M. Drukkaevich), the projective test «The picture of the family» (R. Burns, S. Kaufman), projective method «Man in the rain» (O. Romanova, T. Sytko), projective method «House. Tree. Man» (J. Buck). It was noted that in order to determine the reliable differences in the frequency of expressiveness (presence/absence) of the characteristics of personality and family functioning in parents of problem children, a binomial test was used. It is anticipated that the results will be based on the optimal model of psychological support for both parents and the entire family system, which includes a child with developmental problems. It was investigated that for the female part of parents with problematic children, the following characteristics of personality and family functioning were found: «feeling of instability», «suspicion, distrust», «difficulties in communication and in interaction with others», «anxiety, fear», «impulsiveness», «passivity», «emotional and intellectual immaturity», «sexual problems», «coldness of relationships», «rigidity», «stress», «propensity to avoid problems», «competition between parents or siblings», «uncertainty, self-doubt» . For the male part of parents with problematic children, the following characteristics of personality and family functioning were found: «feeling of instability», «suspicion, distrust», «difficulties in communication and in interaction with others», «anxiety, fear», «satisfaction», «impulsiveness», «passivity», «emotional and intellectual immaturity», «readiness to work on problems», «positive setting for research, family», «coldness of relationships», «rigidity», «stress», «tendency to avoid problems».